Heat and the planning system: how can local authorities encourage deployment of low and zero-carbon heating? - Barns, David G.; Bale, Catherine S. E.; Taylor, Peter G.; Owen, Alice (Frontiers in Sustainable Cities, 2024)
There is widespread recognition of the need for new homes to feature only low or zero-carbon (LZC) heating. However, residential developers continue to choose conventional high-carbon options such as natural gas boilers over net-zero compatible alternatives. This study explores how UK local authorities (LAs) within the English planning system can encourage residential developers to deploy LZC heating systems within their projects. We adopt an embedded case study design and analyse 30 residential project proposals within two LA areas. Our study examines local planning policies and interactions between developers and LA officers, along with the resultant outcomes, through documentary analysis and expert interviews with local stakeholders. We find that LAs can encourage developers to adopt LZC heating technologies above and beyond what is required nationally. The conditions for this to occur are (1) a planning policy which restricts allowable heating technology options, (2) empowering LA officers to enforce policies, (3) advice and support for developers to consider alternatives, and where necessary, (4) political backing to challenge unwilling developers. Study findings highlight the important role of LAs in creating the conditions for the transition to LZC heating, which show how they can use powers within the planning system to encourage developers to make low carbon choices without the need for direct investment.